Which, who and when? Therapeutic processes in group cognitive behaviour therapy for anxiety disorders. (10th April 2022) - Luong, Hoang K.; Roberge, Pasquale; Provencher, Martin D.; Kilby, Christopher J.; Drummond, Sean P. A.; Norton, Peter J.
Abstract: The evidence for the effect of therapeutic alliance in group cognitive behaviour therapy (CBT) for anxiety disorders is unclear. Identifying whether the alliance–outcome relationship depends on (1) which components are assessed, (2) who is measuring the alliance and (3) when the alliance is measured will help to clarify the role of the client–therapist relationship in therapy. The present study explored the effects of alliance component (agreement vs. bond), rater perspective (client vs. therapist) and timing (early vs. late therapy) on the alliance–outcome relationship. Individuals with an anxiety disorder enrolled into transdiagnostic group CBT were studied, with n = 78 at early therapy and n = 57 at late therapy. Results showed that greater client‐rated agreement significantly predicted improved post‐treatment outcomes throughout the course of therapy, while stronger client‐rated bond in late therapy predicted reduced treatment gains. In contrast, therapist perceptions of agreement and bond were not associated with post‐treatment outcomes at any point in therapy. Client‐reported group cohesion also was not associated with additional variance in outcome after accounting for client‐rated alliance. Overall, the findings highlight the importance of prioritizing the client's perception of the client–therapist relationship in CBT for anxiety disorders, as well as distinguishing the effects of component, rater and timing in future process–outcome studies.